Sperm morphological abnormalities in autosomal dominant polycystic kidney disease are associated with the Hippo signaling pathway via PC1 - Shi, Wei-Hui; Zhou, Zhi-Yang; Ye, Mu-Jin; Qin, Ning-Xin; Jiang, Zi-Ru; Zhou, Xuan-You; Xu, Nai-Xin; Cao, Xian-Lin; Chen, Song-Chang; Huang, He-Feng; Xu, Chen-Ming (Frontiers in Endocrinology, 2023)
Background Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary kidney disorder mostly caused by mutations in PKD1 or PKD2 genes. Here, we report thirteen ADPKD males with infertility and investigated the sperm morphological defects associated with PC1 disruption. Methods Targeted next-generation sequencing was performed to detect PKD1 variants in patients. Sperm morphology was observed by immunostaining and transmission electron microscopy, and the sperm motility was assessed using the computer-assisted sperm analysis system. The Hippo signaling pathway was analyzed with by quantitative reverse transcription polymerase chain reaction (qPCR) and western blotting in vitro. Results The ADPKD patients were infertile and their sperm tails showed morphological abnormalities, including coiled flagella, absent central microtubules, and irregular peripheral doublets. In addition, the length of sperm flagella was shorter in patients than in controls of in in. In vitro, ciliogenesis was impaired in Pkd1-depleted mouse kidney tubule cells. The absence of PC1 resulted in a reduction of MST1 and LATS1, leading to nuclear accumulation of YAP/TAZ and consequently increased transcription of Aurka. which might promote HDAC6-mediated ciliary disassembly. Conclusion Our results suggest the dysregulated Hippo signaling significantly contributes to ciliary abnormalities in and may be associated with flagellar defects in spermatozoa from ADPKD patients.